Treatment of Occupational Health Risks in Criminal Prosecution of Abuse of Prostitution in Slovenia - Kogovšek Šalamon, Neža (Medicine, Law & Society, 2024)
The paper explores how occupational and health rights of sex workers are dealt with by courts in criminal proceedings related to the crime of abuse of prostitution under Article 175 of the Slovenian Criminal Code. The authors find that judicial decisions on the crime of abuse of prostitution invariably include considerations regarding occupational health risks, access to health care, and the health rights of sex workers. The paper builds upon the authors’ previous research publications, where they established that in Slovenia, while the restrictive approach to dealing with prostitution prevails, elements of both repressive and integrative approaches are present. Stressing the health rights of sex workers constitutes an integrative approach to prostitution.